2013
DOI: 10.1007/s00535-013-0859-1
|View full text |Cite
|
Sign up to set email alerts
|

Images of Sonazoid-enhanced ultrasonography in multistep hepatocarcinogenesis: comparison with Gd-EOB-DTPA-enhanced MRI

Abstract: In stepwise hepatocarcinogenesis, uptake of Sonazoid starts decreasing later than that of Gd-EOB-DTPA. Although signal reductions on the post-vascular phase of SEUS or hepatobiliary phase of Gd-EOB-DTPA-enhanced MRI suggest HCC, hypoechoic appearance on the post-vascular phase of SEUS might be HCC-specific, particularly progressed HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 25 publications
2
32
0
Order By: Relevance
“…All of these nodules showed hypointensity on the hepatobiliary phase of Gd-EOB-DTPA-enhanced MRI. These results are compatible with the report by Ohama et al [36] that described that most hypovascular well-differentiated HCCs are depicted as an isoechoic nodule during the post-vascular phase of CEUS, whereas almost all hypovascular well-differentiated HCCs show hypointensity on the hepatobiliary phase of Gd-EOB-DTPA-enhanced MRI.…”
Section: Discussionsupporting
confidence: 83%
“…All of these nodules showed hypointensity on the hepatobiliary phase of Gd-EOB-DTPA-enhanced MRI. These results are compatible with the report by Ohama et al [36] that described that most hypovascular well-differentiated HCCs are depicted as an isoechoic nodule during the post-vascular phase of CEUS, whereas almost all hypovascular well-differentiated HCCs show hypointensity on the hepatobiliary phase of Gd-EOB-DTPA-enhanced MRI.…”
Section: Discussionsupporting
confidence: 83%
“…The Kupffer defect is assessed in the Kupffer phase 6-10 min after arterial enhancement of the target nodule. Some investigators have tried to differentiate borderline hepatic nodules using a contrast agent [47,50,51]. According to these studies, although no DNs showed hypoechogenicity in the Kupffer phase, 64-91% of well-differentiated HCCs showed almost complete isoechogenicity.…”
Section: Imaging-based Characterization Of Borderline Hepatic Nodulesmentioning
confidence: 99%
“…Furthermore, approximately 30% of new hypervascular HCCs manifest as nonhypervascular and hypointense nodules on HBP before arterial hypervascularity develops on serial follow-ups with Gd-EOB-DTPA-enhanced MRI [88]. Meanwhile, Ohama et al [51] reported that 31 of 33 hypovascular well-differentiated HCCs showed hypointensity on the HBP of Gd-EOB-DTPA-enhanced MRI, whereas only 3 of 33 hypovascular well-differentiated HCCs were hypoechoic on the Kupffer phase images on the Sonazoid-enhanced US. This study suggests that uptake of Sonazoid starts decreasing later than that of Gd-EOB-DTPA in stepwise hepatocarcinogenesis.…”
Section: Imaging-based Characterization Of Borderline Hepatic Nodulesmentioning
confidence: 99%
“…Focally decreased enhancement in the hepatobiliary phase of Gd-EOB-DTPA-enhanced MRI in the early stage of multistep hepatocarcinogenesis can signal early HCC [9,10,11,12]. Gd-EOB-DTPA-enhanced MRI has been reported to have higher diagnostic accuracy and sensitivity compared with dynamic computed tomography (CT) and now plays an important role in the detection of HCCs [13,14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%